Update on the treatment of non-small-cell lung cancer: focus on the cost-effectiveness of new agents - Vergnenègre A; Borget I; Chouaid C (Dove Medical Press, 2013)
A Vergnenègre,1,4 I Borget,2 C Chouaid3,4 1Service de Pathologie Respiratoire et d'Allergologie, CHU Dupuytren, Limoges, France; 2Etudes et Recherche en Économie de la Santé, Institut Gustave Roussy, Villejuif, France; 3Service de Pneumologie, CHU Saint-Antoine, Paris, France; 4Inserm, U707, Paris, France Background: The incidence of lung cancer and the cost of drug treatment have increased dramatically in the last decade. This article examines the costs of new target agents, such as tyrosine kinase inhibitors (TKIs) and anti-angiogenic drugs. Methods: This study uses PubMed research to focus on the topics of lung cancer, economics, and new targeted therapies. Results: The published papers only addressed TKIs and anti-angiogenic antibodies. For gefitinib, the results favored a clinical-based selection, despite the low number of studies. Erlotinib was studied in second line and as a maintenance treatment (with the studies reaching opposite conclusions in terms of cost-effectiveness). Economic analyses were not in favor of bevacizumab, but the studies on this topic were very heterogeneous. Conclusion: The economic impact of a drug depends on the health care system organization. Future clinical trials must include economic analyses, particularly with TKIs in the first line. Keywords: lung cancer, new target agents, tyrosine kinase inhibitors, anti-angiogenic, bevacizumab